Islamic Law and Custom in the Land of Bima: A Study in the History of the Government of the Bima Sultanate - Amrin; Sugiyarto; Abdurahman; Mas’udatul Fitriyah (Journal of Islamic History and Manuscript, 2025)
Islamic law and customary law in the Bima Sultanate are two pillars that coexist and complement each other in creating a just and socially acceptable legal system. This study aims to examine the relationship between Islamic and customary law in the history of the Bima Sultanate government, focusing on integrating the two legal systems in the socio-political life of the Bima community. This study uses a historical approach and qualitative methods with a literature review, this study examines various sources of literature that can be accounted for their validity, such as the Bo' Sangaji Kai Chronicle, Abdul Gani Abdullah's work on religious slavery, and books by Henri Chambert Loir, Alan Malingi, and Muhammad Mutawali. This study leads to the critical role of the Syara' Assembly as an institution that integrates Islamic law into the structure of government, as well as the position of the Mufti/Qadhi, which is parallel to the Ruma Bicara, as a form of strengthening collaboration between religious law and customary law in government. Through harmonizing Islamic values and local wisdom, the Bima Sultanate created an inclusive and just legal system, which could answer the social and cultural challenges of the Bima community.